Anti-caries effect of resin infiltrant modified by quaternary ammonium monomers. (June 2020) - Yu, Jinzhao; Huang, Xiaoyu; Zhou, Xuedong; Han, Qi; Zhou, Wen; Liang, Jingou; Xu, Hockin H.K.; Ren, Biao; Peng, Xian; Weir, Michael D.; Li, Mingyun; Cheng, Lei
Graphical abstract: Abstract: Objectives: Resin infiltrant is used in early enamel caries. However, commercial resin infiltrant lacks persistent antibacterial activity. Dimethylaminododecyl methacrylate (DMADDM) was added to resin infiltrant to give it sustainable antibacterial properties and inhibit demineralization. Methods: After the application of resin infiltrant to bovine enamel, cytotoxicity, surface roughness, and aesthetics were assessed. A multi-species biofilm was incubated on the enamel disk before and one month after microbial-aging. After a 48-h anaerobic incubation, biomass accumulation, metabolic activity, and lactic acid were analyzed using a crystal violet assay, an MTT (3-(4, 5-dimethyl-thiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay, and a lactic acid assay. Biofilm structure and composition were determined by live/dead staining, exopolysaccharide (EPS) staining, scanning electron microscopy (SEM), and quantitative polymerase chain reaction (qPCR). The depth and content of demineralization were tested by transverse microradiography (TMR). Results: Incorporating DMADDM did not increase the cytotoxicity or change the physical properties when the mass fraction of the DMADDM was 2.5–10 %. The modification decreased the amount of bacterial biofilm, metabolic activity, lactic acid production, EPS, and the proportion of Streptococcus mutans in the biofilms. It also provided anti-demineralization effects. The surface roughness and antibacterial ability were not changed after one month of microbial-aging. Conclusion: The incorporation of DMADDM improved the antibacterial and anti-demineralization effects of the material. It demonstrated a sustained antibacterial effect. Clinical significance: The antibacterial modification might be a potential choice for future clinical applications to inhibit early enamel caries.